Factors Associated with Behaviors to Prevent and Reduce the Spread of COVID-19 among Storage and Distribution Employees at a Distribution Center - Silangam, Wasana; Sirijaroongwong, Umarat; Kongkarak, Wanna; Wangsri, Napat (Journal of Health Sciences and Wellness, 2025)
Distribution center employees were another group at risk for COVID-19 infection, especially storage and distribution employees. As consumers are increasingly ordering products online, employees are being exposed to a large number of products from both domestic and international locations. This cross-sectional study aimed to study factors associate with prevent and reduce the spread of COVID-19 behaviors among storage and distribution employees at a distribution center. 130 employees participated in the study. The accidental sampling used in this research. The research instruments were the questionnaires about the knowledge of COVID-19 prevention, the attitudes toward COVID-19, the perceived severity of COVID-19, and the prevent and reduce the spread of COVID-19 behaviors which their reliabilities were 0.92, 068, 0.75 and 0.91 respectively. Data were analyzed by descriptive statistics, Chi-square test and Spearman rank correlation coefficient. The results indicated that 76.92% of the participants were females; the mean age was 25.63±3.64 years old, 86.15% had a high level of knowledge, 88.46% had a good level of attitude, 97.69% had a high level of perception disease severity, and 98.46% had a good level of behaviors. Behaviors to prevent and reduce the spread of COVID-19 were significantly positively correlated with the age of work, the average monthly income and the perception disease severity of the COVID-19 (r=0.39, p-value<0.01; r=0.55, p-value<0.01 and r=0.29, p-value<0.01, respectively). To promote prevention and reduce the spread of the COVID-19 behaviors among employee, agencies should regular surveillance, awareness and provide information about the COVID-19.